2019
DOI: 10.22190/fuwlep1803241o
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radioactivity Levels and Transfer Factor of Natural Radionuclides Around Iron and Steel Smelting Company Located in Fashina Village, Ile-Ife, Osun State, Nigeria

Abstract: This study assessed the radioactivity levels and transfer factor of natural radionuclides around iron and steel smelting company located in Fashina village, Ile-Ife, Osun State, Nigeria. This was with a view to evaluate the exposure rate of the study area, determine the radionuclides present and activity concentration (238U and 232Th and 40K) in the samples and evaluate the soil-to-food transfer ratio of the radionuclides. A portable survey meter with a Global Positioning System (GPS) were used for in-situ inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
2
5
2
Order By: Relevance
“…The bioaccumulation factors estimated are 0.49, 0.46 and 0.58 respectively for 40 K, 238 U and 232 Th. These values are comparable with the findings of Oluyide et al (2018). The presence of the radionuclides in high concentration in the grains is a call for serious concern because their high activity concentration can bring about internal exposure to ionizing radiation which is very detrimental to human health.…”
Section: Resultssupporting
confidence: 88%
“…The bioaccumulation factors estimated are 0.49, 0.46 and 0.58 respectively for 40 K, 238 U and 232 Th. These values are comparable with the findings of Oluyide et al (2018). The presence of the radionuclides in high concentration in the grains is a call for serious concern because their high activity concentration can bring about internal exposure to ionizing radiation which is very detrimental to human health.…”
Section: Resultssupporting
confidence: 88%
“…The results were classified according to the correlation coefficient R (49) , as follows: A somewhat weak correlation of 0.3130 exists between gamma dose rate (DR) and 40 K, a moderately significant correlation of 0.6633 exists between DR and 238 U and a significant correlation of 0.7225 as found to exist between DR and 232 Th. The correlation results showed that the mine field is loaded with uranium and thorium, with 232 Th contributing more signi significant to the gamma dose received from the field than 238 U and 40 K. These radionuclides have been noted for their notorieties and contributions to background ionizing radiation which is linked with various kinds of cancers, liver diseases and ruthless health related harms which could eventually lead to death (16,17,19,50,51,52) .…”
Section: Resultsmentioning
confidence: 99%
“…These elements when introduced into the environment by activities like the one taking place at Ipata Oloje automobile spare part and recycling market, usually find their way into human bodies to an extent via ingestion of soil (dust) particle, through food chain, drinking of contaminated water and dermal contact [8][9][10] . Some of these HMs are vital to human life as sources of minerals and vitamins, and/or play irreplaceable physiological roles in the human body, but become toxic at higher concentration and can therefore result to poisoning at relatively high concentrations 6 .…”
mentioning
confidence: 99%